To calculate \((f \cdot g)(x)\), we need to multiply the two functions \(f(x) = x\) (the length) and \(g(x) = x + 3\) (the width).
\[ (f \cdot g)(x) = f(x) \cdot g(x) = x \cdot (x + 3) \]
Now, distributing \(x\):
\[ (f \cdot g)(x) = x^2 + 3x \]
This expression \(x^2 + 3x\) represents the area of the rectangle since the area is calculated by multiplying the length and width.
Therefore, the correct response is:
\((f \cdot g)(x) = x^2 + 3x; \text{ It represents the area of the rectangle in square feet.}\)